2008
DOI: 10.1016/j.apsoil.2008.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Soil biological quality after 36 years of ley-arable cropping, permanent grassland and permanent arable cropping

Abstract: Nematodes Microbiology Soil biotaCrop rotation Grassland a b s t r a c tInsight is needed into how management influences soil biota when sustainable grassland systems are developed. A crop rotation of grass and maize can be sustainable in terms of efficient nutrient use. However, there is lack of information on the effect of such a crop rotation on soil biological quality. Earthworms, nematodes, bacteria and fungi were sampled over three years in a 36 years old experiment. Permanent arable land was compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
64
3
13

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(86 citation statements)
references
References 52 publications
6
64
3
13
Order By: Relevance
“…The permanent arable system was in maize. Adapted from van Eekeren et al 31 approach can be followed, designing agricultural plant communities to achieve specific functions or combinations of functions rather than simply 'piling on' species to achieve diversity in numbers only 45 . Management of highly diverse grasslands to deliver multiple ecosystem services (e.g., soil C storage, biodiversity conservation and enhanced nutrient cycling) in addition to herbage production will likely require trade-off among services and well-designed economic incentives for farmer adoption 46 .…”
Section: Management Tools Needed For Diverse Mixturesmentioning
confidence: 99%
“…The permanent arable system was in maize. Adapted from van Eekeren et al 31 approach can be followed, designing agricultural plant communities to achieve specific functions or combinations of functions rather than simply 'piling on' species to achieve diversity in numbers only 45 . Management of highly diverse grasslands to deliver multiple ecosystem services (e.g., soil C storage, biodiversity conservation and enhanced nutrient cycling) in addition to herbage production will likely require trade-off among services and well-designed economic incentives for farmer adoption 46 .…”
Section: Management Tools Needed For Diverse Mixturesmentioning
confidence: 99%
“…PCA results indicated that organic matter, total organic carbon, carbon content and cation exchange capacity have strong positive relationship which explains that the nutrients in the soil are stored in organic matter. Suitable range of relative humidity or carbon content in soil will enhance organic matter breakdown by soil microbes (Van Eekeren et al, 2008). Hence, tree roots will be able to absorb nutrients released from the organic matter for growing and maturity.…”
Section: Identifying the Important Soil Properties At Rehabilitated Fmentioning
confidence: 99%
“…Droughts are the main source of inter-annual variation in terrestrial C sequestration, as they cause large reductions in GPP as well as in the net ecosystem exchange (NEE) of terrestrial ecosystems [26,27]. Droughts also have negative effects on soil biodiversity, the content of SOM, and water retention [28]; they may have implications on ecosystem functions that last longer than the drought itself [29,30]. Most notably, the ecosystem C sequestration accumulated over a number of years could be undone by a single severe drought [26,31].…”
Section: Drought and Grassland C Cyclingmentioning
confidence: 99%